2006
DOI: 10.1111/j.1744-313x.2006.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G polymorphism in a Chinese Han population with recurrent spontaneous abortion

Abstract: Reproduction is an important biological phenomenon posing an immunological paradox because the semiallogeneic fetus survives by evading maternal immune recognition. The detailed mechanisms behind this maternal-fetal immunotolerance remain elusive. Human leucocyte antigen (HLA)-G, a non-classical HLA class I antigen, initially identified as a molecule selectively expressed on extravillous cytotrophoblasts and first studied in the context of pregnancy, has long been supposed to play a critical role in fetal-mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
4
26
0
1
Order By: Relevance
“…A similar Chinese study reported the same results [67]. Other studies have not reported significant associations between the 14-bp HLA-G polymorphism (or other HLA-G alleles) and RSA or in vitro fertilization [25,68]. Two studies have investigated the hypothesis of HLA-G histoincompatibility or sharing of alleles between a woman and her partner, and thus the fetus, but reported no support for this [62,69].…”
Section: Hla-g Polymorphism In Relation To Pregnancy Complicationsmentioning
confidence: 49%
“…A similar Chinese study reported the same results [67]. Other studies have not reported significant associations between the 14-bp HLA-G polymorphism (or other HLA-G alleles) and RSA or in vitro fertilization [25,68]. Two studies have investigated the hypothesis of HLA-G histoincompatibility or sharing of alleles between a woman and her partner, and thus the fetus, but reported no support for this [62,69].…”
Section: Hla-g Polymorphism In Relation To Pregnancy Complicationsmentioning
confidence: 49%
“…Furthermore, the +14 bp/+14 bp genotype was found in RSA patients with abortions greater than 3 as observed byAbbas et al .,[11] Tripathi et al .,[12] and Yan et al . [13] They showed an increase in the frequency of 14-bp insertion alleles in the RSA group as compared to controls whereas in contrast, Hviid et al . [19] observed more number of heterozygotes in controls.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies did not find any association between HLA-G and recurrent spontaneous abortion [65,[85][86][87][88][89] or preeclampsia [90][91][92]. However, significant associations between HLA-G*01:05N, HLA-G*01:01:03 and HLA-G*01:04 alleles and recurrent spontaneous abortion have been documented in Caucasian populations [79,93], and in French and Chinese populations, the HLA-G*01:06 allele has been associated with preeclampsia [94,95].…”
Section: Hla-g and Pregnancy Disorders (Recurrent Pregnancy Loss Prementioning
confidence: 97%
“…Yan et al, [87] recurrent spontaneous abortion PCR significantlyincreasedfrequencyof-14bp/+14bp heterozygotes in RSA patients compared to normal fertile controls of Chinese ethnicity…”
Section: Diseasementioning
confidence: 99%